ANALISIS ELEMEN BRAND EQUITY DAN HUBUNGANNYA DENGAN LOYALITAS PELANGGAN PRODUK EIGER - Tika Rahmawati; Aminuyati Aminuyati; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study is a research that aims to analyze the perception of brandequity elements and their relationship with customer loyalty of Eigerproducts to students of Economics Education FKIP Untan. Themethod used in this study is a qualitative research approach, namelyresearch procedures that utilize descriptive data in the form of writtenor spoken words from observable people and actors. The form ofresearch used is a case study. The object of this research is theeconomic education student of FKIP Untan who has previously filledout a google form to complete pre-research data and is looking forEiger users with the criteria of having at least 2 Eiger products. Thenumber of students who became informants in this study were 11people. The results obtained are all elements of brand equity havepositive perceptions of users, in this case students of EconomicsEducation FKIP Untan.